2017
DOI: 10.1002/anie.201709199
|View full text |Cite
|
Sign up to set email alerts
|

O2 Activation on Ceria Catalysts—The Importance of Substrate Crystallographic Orientation

Abstract: An atomic-level understanding of dioxygen activation on metal oxides remains one of the major challenges in heterogeneous catalysis. By performing a thorough surface-science study of all three low-index single-crystal surfaces of ceria, probably the most important redox catalysts, we provide a direct spectroscopic characterization of reactive dioxygen species at defect sites on the reduced ceria (110) and (100) surfaces. Surprisingly, neither of these superoxo and peroxo species was found on ceria (111), the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
129
2
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(154 citation statements)
references
References 50 publications
14
129
2
1
Order By: Relevance
“…[131] The carbenec omplexs pontaneously reacts with CH 4 to yield the complex with two methyl groups (CH 3 ) 2 Ti(H)(OH), whichi sa lso formed directly by UV irradiation of (CH 3 )Ti(H)(O)(CH 4 ). For CH 3 Cl, insertion into the CÀ Hb ond as well as the CÀCl bond is observed. ScO reacts with CH 3 Cl to yield at first the ScO(CH 3 Cl) complex, and after irradiation both CH 3 OScCl and CH 2 ClScOH.…”
Section: Reactions Of Mo Clusters In Matricesmentioning
confidence: 97%
See 3 more Smart Citations
“…[131] The carbenec omplexs pontaneously reacts with CH 4 to yield the complex with two methyl groups (CH 3 ) 2 Ti(H)(OH), whichi sa lso formed directly by UV irradiation of (CH 3 )Ti(H)(O)(CH 4 ). For CH 3 Cl, insertion into the CÀ Hb ond as well as the CÀCl bond is observed. ScO reacts with CH 3 Cl to yield at first the ScO(CH 3 Cl) complex, and after irradiation both CH 3 OScCl and CH 2 ClScOH.…”
Section: Reactions Of Mo Clusters In Matricesmentioning
confidence: 97%
“…Ga 2 H 2 .H owever,t he detailedq uantum chemical study by Kçhn et al [39] showed that the reaction is able to proceed via asmall barrier by an intersystem crossing to the singlet potential energy surface. At first, due to the reduced symmetry of the system during the approacho ft he reactants, am ixingb etween the original 3 ). Hence, resultsshow that two low-lying excited electronic states of Ga 2 are important during the courseo ft he reaction.…”
Section: Why Do Clusters Have Such An Unusual Reactivity?mentioning
confidence: 99%
See 2 more Smart Citations
“…Herein, we report a simple, additive‐free and reusable heterogenous catalytic system based on CeO 2 for the direct phenolysis of unactivated amides into the corresponding phenolic esters. A systematic mechanistic study revealed that the unique combination of acid/base and redox properties of CeO 2 promotes this esterification reaction. This catalytic system not only offers a facile means to cleave the amide C−N bond, but also significantly promotes the use of amides and phenols as important building blocks for the synthesis of valuable esters.…”
Section: Introductionmentioning
confidence: 99%